Effects of environmentally relevant ibuprofen exposure on ovarian follicular atresia in Wistar rats: A biochemical and immunohistological study - Safa Mouaki Benani; Souheyla Benbia; Yamina Belkhiri; Kahina Yahia; Angham Ouadah; Aya Chafai (Clinical and Experimental Reproductive Medicine, 2026)
Objective: This study aimed to investigate whether chronic exposure to environmentally relevant concentrations of ibuprofen promotes follicular atresia in female rats and to explore potential underlying mechanisms affecting ovarian function.Methods: Ten adult female Wistar rats were randomly assigned to two groups (n=5 per group): a control group and an ibuprofen-exposed group. The experiment was conducted over a 4-month period. The control group received standard drinking water, whereas the ibuprofen group received drinking water supplemented with ibuprofen. Body weight and ovarian index were recorded throughout the study. Ovarian tissues were examined histologically to quantify atretic follicles and to assess structural alterations. Immunohistochemical analysis was performed to evaluate B-cell lymphoma 2 (Bcl-2) expression. Biochemical analyses were conducted to measure oxidative stress markers, including malondialdehyde and catalase, and serum levels of estradiol and interleukin 6 (IL-6) were determined.Results: Chronic ibuprofen exposure was associated with a significant increase in follicular atresia and induced marked histopathological alterations in ovarian tissue. Both body weight gain and the ovarian index were reduced in the ibuprofen group compared with controls. Biochemical analyses demonstrated elevated oxidative stress, along with disrupted serum estradiol and IL-6 levels. In addition, Bcl-2 expression was downregulated in ibuprofen-exposed rats.Conclusion: Even at environmentally relevant concentrations, ibuprofen exposure may compromise ovarian function by promoting follicular atresia through multiple interacting pathways, including oxidative stress, inflammatory responses, downregulation of Bcl-2, and impaired estradiol synthesis. These findings highlight the potential reproductive health risks associated with chronic low-dose environmental exposure to ibuprofen.